Bone healing in critical-size defects treated with platelet-rich plasma: a histologic and histometric study in rat calvaria - Messora, M. R. [UNESP]; Nagata, Maria José Hitomi [UNESP]; Mariano, R. C.; Dornelles, Rita Cássia Menegati [UNESP]; Bomfim, Suely Regina Mogami [UNESP]; Fucini, S. E. [UNESP]; Garcia, Valdir Gouveia [UNESP]; Bosco, Álvaro Francisco [UNESP] (Blackwell Publishing, 2008)
Background and objective: The purpose of this study was to analyze histologically the influence of autologous platelet-rich plasma on bone healing in surgically created critical-size defects in rat calvaria.Material adn Methods: Thirty-two rats were divided into two groups: the control group (group C) and the platelet-rich plasma group. An 8-mm-diameter critical-size defect was created in the calvarium of each animal. In group C the defect was filled by a blood clot only. In the platelet-rich plasma group, 0.35 mL of platelet-rich plasma was placed in the defect and covered by 0.35 mL of platelet-poor plasma. Both groups were divided into subgroups (n = 8) and killed at either 4 or 12 wk postoperatively. Histometric (using image-analysis software) and histologic analyses were performed. The amount of new bone formed was calculated as a percentage of the total area of the original defect. Percentage data were transformed into arccosine for statistical analysis (analysis of variance, Tukey, p < 0.05).Results: No defect completely regenerated with bone. The platelet-rich plasma group had a statistically greater amount of bone formation than group C at both 4 wk (17.68% vs. 7.20%, respectively) and 12 wk (24.69% vs. 11.65%, respectively) postoperatively.Conclusion: Within the limits of this study, it can be concluded that platelet-rich plasma placed in the defects and covered by platelet-poor plasma significantly enhanced bone healing in critical-size defects in rat calvaria.
Keywords: bone regeneration; growth factors; in vivo model; platelets